Comparative Study between Dermo, Pelite, and Seal-In X5 Liners: Effect on Patient's Satisfaction and Perceived Problems. (11th August 2014) - Ali, Sadeeq; Abu Osman, Noor Azuan; Arifin, Nooranida; Gholizadeh, Hossein; Abd Razak, Nasrul Anwar; Wan Abas, Wan Abu Bakar
Abstract : Purpose . This study aimed to compare the effect of satisfaction and perceived problems between Pelite, Dermo with shuttle lock, and Seal-In X5 liners on the transtibial amputees. Material and Methods . A total of thirty transtibial amputees (17 male, 13 female) volunteered to take part in this research. Two prostheses were fabricated for each participant. Prosthetic Evaluation Questionnaire (PEQ) was filled in by the participants with the three liners. Results . The statistics highlight that Dermo liner showed significantly higher score (P = 0.05 ) in walking, walking on uneven surfaces, stairs walking, fitting, donning/doffing, sitting, suspension, and overall satisfaction with Dermo liner compared with Seal-In X5 and Pelite liners. Overall satisfaction was 34% higher with Dermo liner than Seal-In X5 liner and 28% higher than Pelite liner. Participants reported less problems with Dermo liner and significant differences (P < 0.05 ) were recorded between the three liners in sweating, skin irritation, frustration, and pain compared with Seal-In X5 and Pelite liners. Conclusion . Participants experienced high level of satisfaction and practiced fewer problems with Dermo liner. These results showed that there is good indication to believe that Dermo liner might be a good choice for transtibial users and might help the clinicians and prosthetic practitioners in selection criteria of prosthetic liners.